Pengaruh Gaya Belajar, Aktivitas, dan Perhatian Orang Tua Terhadap Prestasi Belajar IPAS Siswa SD di Boyolangu - Winarti, Lilik; Afifah, Dian Septi Nur; Dirgantoro, Ajar (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to analyze the relationship between learning styles, learning activities, and parental attention with the learning achievement of fifth-grade elementary school students in Natural and Social Sciences (IPAS) in Boyolangu District, Tulungagung Regency. This study used a quantitative approach with a correlational design. The sample size was 151 students drawn using simple random sampling from four public elementary schools. Data collection used questionnaires and academic grade documentation, while data analysis was conducted through multiple linear regression. The results showed that all three independent variables had a positive and significant relationship with learning achievement, both partially and simultaneously. Partially, learning styles had a significance value of 0.009 with a correlation coefficient of r = 0.491 (moderate category), learning activities had a significance value of 0.001 with r = 0.498 (moderate category), and parental attention showed the strongest influence with a significance value of 0.003 and r = 0.894 (strong category). Simultaneously, all three variables had a significant relationship with academic achievement (significance 0.002), although the strength of the relationship was moderate (R = 0.308). This finding indicates that student academic success depends not only on internal factors such as learning styles and activities, but is also significantly influenced by parental support at home. The practical implication of this study is the importance of collaboration between teachers and parents in designing learning strategies responsive to student characteristics to improve the quality of science learning outcomes in elementary schools.